Similar rates of denial in NICHD and control interviews with alleged child abuse victims in the Netherlands - Bücken, Charlotte A. (Legal and criminological psychology, 2024)
Purpose In the current study, we investigated whether denial and avoidance rates differed statistically significantly based on the interview protocol used. Method We examined 38 National Institute of Child Health and Human Development (NICHD) interview transcripts, and 30 control transcripts from interviews from an earlier study (Applied Cognitive Psychology, 2022, 36, 7) conducted with alleged child victims of abuse at Dutch child protection services. Results We detected 57 denial and 282 avoidance statements across the 68 interviews. No statistically significant differences emerged between (1) the proportion of denials using NICHD (42%, n = 16/38) and control interviews (30%, n = 9/30), and (2) the average number of denial statements between NICHD (M = 0.84) and control interviews (M = 0.83). Furthermore, denials (and avoidances) were not more or less likely to occur in response to certain types of questions, even though the majority of denials in our sample occurred in response to option-posing questions (60%, n = 34/57). Denials did occur statistically significantly less often within the first half of the individual interviews in NICHD than in control interviews. Conclusions Our findings call attention to the difficulties child protection services face in investigative interviews with alleged child victims.